1994
DOI: 10.1172/jci117375
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal expression of laminin suggests disturbance of sarcolemma-extracellular matrix interaction in Japanese patients with autosomal recessive muscular dystrophy deficient in adhalin.

Abstract: Dystrophin is associated with several novel sarcolemmal proteins, including a laminin-binding extracellular glycoprotein of 156 kD (a-dystroglycan) and a transmembrane glycoprotein of 50 kD (adhalin). Deficiency of adhalin characterizes a severe autosomal recessive muscular dystrophy prevalent in Arabs. Here we report for the first time two mongoloid (Japanese) patients with autosomal recessive muscular dystrophy deficient in adhalin. Interestingly, adhalin was not completely absent and was faintly detectable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The resulting amino acid substitutions are expected to reduce the hydrophilicity of the protein, and furthermore the substitution of Arg by Cys with a sulfhydryl radical (-SH) and the insertion of five amino acids would probably affect the secondary and tertiary structures of adhalin. These could disturb its interaction with other membrane-associated proteins or the components of the basal lamina (16,(26)(27)(28)(29)(30). It is also conceivable that alteration of the higher order structure of mutant adhalin may cause its rapid degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting amino acid substitutions are expected to reduce the hydrophilicity of the protein, and furthermore the substitution of Arg by Cys with a sulfhydryl radical (-SH) and the insertion of five amino acids would probably affect the secondary and tertiary structures of adhalin. These could disturb its interaction with other membrane-associated proteins or the components of the basal lamina (16,(26)(27)(28)(29)(30). It is also conceivable that alteration of the higher order structure of mutant adhalin may cause its rapid degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency of adhalin (a 50-kD dystrophin-associated glycoprotein) in the skeletal muscle has been found in several families with SCARMD (12)(13)(14)(15)(16). Recently, complete absence of adhalin in skeletal muscle and missense mutations in the adhalin gene were identified in a single French family with autosomal recessive muscular dystrophy which was less clinically severe than SCARMD (17).…”
Section: Introductionmentioning
confidence: 99%
“…4, C and D). Since both proliferative myoblasts and differentiated myotubes express the ␣7B integrin subunit (37-41), the apparent increased sarcolemmal expression of this subunit may be the result of enhanced myoblast fusion with actively regenerating dystrophic myofibers (11)(12)(13)(14)(15)(16)(17). Thus, these data indicate that the loss and/or disruption of ␣7␤1D integrin isoforms in striated muscle is correlated specifically to merosin deficiency, and is not an overall consequence of muscular dystrophy.…”
Section: The Distribution Of ␣7␤1d Integrin Isoforms Is Abnormal In Mmentioning
confidence: 93%
“…Mutations in the gene for the ␣ 2 chain ( LAMA2 ) of merosin, which lead to either a loss of expression or to the expression of a defective molecule, have been shown to cause a severe form of autosomal recessive congenital muscular dystrophy (CMD) termed merosin-deficient CMD (MCMD; 2, 4, 8, 10). A reduction in merosin ␣ 2 and/or ␤ 1/ ␤ 2 chains has been observed in other muscular dystrophies, such as the Fukuyama congenital muscular dystrophy (FCMD), the Finnish muscle-eye-brain disease (MEB), and the Walker-Warburg syndrome (4,(11)(12)(13)(14). However, the genetic defects responsible for these other diseases have yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological role of each sarcoglycan protein and the pathophysiology of sarcoglycanopathy are poorly understood. Wehave reported that there is reduction of the beta-1 subunit of laminin, heparan sulfate proteoglycan (HSPG), and HCAM in*Japanese patients with sarcoglycanopathy (6)(7)(8). The expression of the CD24molecule, a glycoprotein expressed on the surface of most B lymphocytes and differentiating neuroblasts, was reported to be associated with a subpopulation of regenerative fibers in diseased muscles (9).…”
Section: Introductionmentioning
confidence: 99%